Reproductive biology of Symphodus mediterraneus (Teleostei, Labridae) in the Azores - Raposeiro, Pedro M. (2009)
A description of the colour patterns, reproductive behaviour, spawning season and size at first maturity is given for an Atlantic population of Symphodus mediterraneus, based on underwater observations and animals collected by spear-fishing and photographed. Gonad histology was used to determine the sex and maturity stages. Size at first maturation was estimated as the length at which 50% of the individuals are mature. General appearance was a brown or brownish-red body, with a series of large brown transverse stripes, a conspicuous yellow-ringed black spot on the base of the pectoral fins and a black spot on the caudal peduncle. Terminal males could be distinguished from females by the blue tones on the extremities of the median fins and on the throat. Differences from the colour pattern of the Mediterranean population are noted. This is probably a gonochoric species: the larger males are territorial, building algal nests and defending them from conspecific males and from other microbenthic carnivorous fishes; the smaller mature males did not show sneaking or satellite behaviour. Reproduction takes place in late spring and summer, after the spring productivity peak, suggesting that the feeding biology of the adults may be the main determinant factor of the timing of spawning. Total length at first maturity is 12.1 cm for males and 9.6 cm for females.